Step-by-step explanation:
Let's take cost of 1 hamburger as h and the cost of 1 hot dog as d.
Therefore, we can form the equations:
3h + 2d = 13 and
2h + 4d = 14
2(h +2d) = 14
h + 2d = 7
h = 7 - 2d
By substituting this to the first equation, we get:
3(7 - 2d) + 2d = 13
21 - 4d = 13
4d = 8
d = $2
h = 7 - 2(2)
h = $3
Hence <u>1 hot dog costs $2</u> and <u>1 hamburger costs $3</u>
Answer:
Let the angle=x
So the other angle will be = y
X-28 +y=90
15 times 3 equals 45 hoped i helped
Answer:
Multiply the second equation by −2 to get −8x − 6y = −30.
Step-by-step explanation:
{2x + 6y = 12
{4x + 3y = 15
{2x + 6y = 12
{−8x − 6y = −30 >> New Equation
* Doing this will give you <em>additive</em><em> </em><em>inverses</em><em> </em>of −6y and 6y, which result in 0, so they are both ELIMINATED.
** [3, 1] is your solution.
I am joyous to assist you anytime.
Answer:
10.5
Step-by-step explanation:
1.5 inches
.5 and 1.5 =3
3x3.5=10.5